Exploring the role of health consciousness and environmental awareness in purchase intentions for green-packaged organic foods: an extended TPB model - Li, Youyou; Shan, Baoshun (Frontiers in Nutrition, 2025)
BackgroundWith the increasing rise of green consumption concepts, consumers are becoming more concerned with the health and environmental attributes of products. However, research on purchase intentions for green-packaged organic foods remains relatively limited, particularly regarding the specific impact of health consciousness and environmental awareness. There is a clear gap in the literature addressing these factors.MethodBased on the Theory of Planned Behavior (TPB), this study constructs a relationship model between health consciousness, environmental awareness, attitude, subjective norms, perceived behavioral control, and purchase intentions for green-packaged organic foods. A total of 372 valid survey samples were collected, and data analysis was performed using SPSS 26.0 and AMOS 28.0 software to validate the theoretical model and research hypotheses.ResultsStructural equation modeling (SEM) analysis reveals that all hypotheses are significantly supported, and the model demonstrates good fit. Mediation effect analysis further reveals the impact of health consciousness and environmental awareness on purchase intentions, indicating that they influence consumer intentions indirectly through attitudes, subjective norms, and perceived behavioral control.ConclusionHealth consciousness and environmental awareness not only significantly affect consumers’ purchase intentions for green-packaged organic foods through direct paths but also have important indirect effects through attitudes, subjective norms, and perceived behavioral control. This study provides a new perspective for the theoretical development of green consumer behavior and offers valuable practical insights for businesses and policymakers in promoting green consumption and sustainable products.